The kinetic of dilute-acid hydrolysis of agrowaste for the production of reducing sugar - Razali, Firdausi; Lee, Chew Tin; Mat, Ramli (Faculty of Chemical and Natural Resource Engineering, 2009)
There is a growing incentive for us to identify alternative and ideally renewable energy sources. Among the sources, grains, plant matters (biomass) and their wastes are commonly been used for biofuel production due to their sustainability. Oil palm empty fruit bunch (EFB) is a type of lignocellulosic waste from palm oil mills. Fermentable sugars mainly the glucose from EFB can be further fermented for the production of bioethanol. This study aims to investigate the effect of the key parameters during dilute acid pretreatment and enzymatic treatment for the hydrolysis of EFB to produce optimised yield of glucose. Three parameters for the dilute acid pretreatment, namely the reaction temperature, acid concentration and reaction time and two parameters for the enzymatic treatment, namely the substrate concentration and treatment time were investigated to optimise the yield of glucose. Batch reactions were carried out under different combination of operational conditions as proposed by the experimental design produced by the RSM (response surface methodology). RSM was used to optimise both the pretreatment and enzymatic processes in order to obtain the highest glucose yield. An optimised glucose yield of 53.96 % was obtained at the operating condition of 130 Â°C pretreatment temperature, 6 %w/w sulphuric acid concentration, 37 min of pretreatment time and 96 hours of enzymatic treatment using 6 %w/v of substrate concentration. The optimised yield has also been validated through experiment work.